Molecular identification and seasonal infections of species of Fasciola in ruminants from two provinces in China. Issue 3 (30th June 2015) - Yuan, W.; Liu, J.-M.; Lu, K.; Li, H.; Duan, M.-M.; Feng, J.-T.; Hong, Y.; Liu, Y.-P.; Zhou, Y.; Tong, L.-B.; Lu, J.; Zhu, C.-G.; et al.
Abstract: We determined the prevalence and seasonality of infections by Fasciola of goats and bovine species (cattle and water buffalo) in Hubei and Anhui provinces of China. Faecal samples were collected at 2- to 3-month intervals from 200 goats in Hubei province and from 152 bovine species in Anhui province. All faecal samples were examined for the presence of parasites. We determined the nucleotide sequences of the first and second internal transcribed spacers (ITS-1 and ITS-2) of the nuclear ribosomal DNA (rDNA) of 39 Fasciola worms from Anhui province. The prevalence of Fasciola infection in goats ranged between 3.5 and 37.0%, with mean eggs per gram (EPG) ranging between 29.0 and 166.0. Prevalence and EPG exhibited downward trends over time with significant differences. The prevalence of Fasciola infection in cattle ranged between 13.3 and 46.2% (mean EPG, 36.4–100.0), and that of water buffalo ranged between 10.3 and 35.4% (mean EPG, 25.0–89.6), with a higher prevalence of infection and EPG from June to October compared with December to March. Analysis of ITS-1 and ITS-2 sequences revealed that F. hepatica and F. gigantica were present in all bovine species of Anhui province and that F. gigantica mainly infected water buffalo. This is the first demonstration of Fasciola infection in Hubei province and detection of F. hepatica and F. gigantica in Anhui province. The present study of Hubei province shows that mass treatment of livestock with closantel sodium injections in April and August/September controlled Fasciola infection effectively.